The Prevalence of Hypothyroidism in Patients with Biliary Sludge and Gallstones - Raheleh Jabini; Seyed Musa al-Reza Hosseini; Maryam Shirdeli; Ali Alabaf Yousefi; Mohamadreza Farzanehfar (Reviews in Clinical Medicine, 2020)
Introduction: Gallbladder stone and sludge are common diseases worldwide. The causes of gallbladder stone and sludge are numerous. Since some studies have reported the effects of thyroid hormones on the function of the sphincter of Oddi and biliary discharge, the present study aimed to evaluate hypothyroidism as a risk factor for gallbladder stone formation.Methods: This case-control study was conducted on patients whose sonography indicated gallbladder sludge or stone and those referring to our clinic with pain in the right upper quadrant of the abdomen. All the patients were initially examined by a sonologist to confirm gallbladder stone and sludge. Afterwards, thyroid function tests (TSH, T4, and T3RU via radioimmunoassay) were requested for the patients, and the results were analyzed and compared with the control group.Results: Among 318 patients, 171 (53.77%) were male. In the case group, six females (8.4%) and 10 males (11.2%) had hypothyroidism. Overall, 9.9% of the patients (n=16) had hypothyroidism. In the control group, the prevalence of hypothyroidism was 2.5% (n=4) (OR: 2.082; 95% CI: 1.022-11.046; P=0.017). In the case group, 4.3% (n=7) had subclinical hypothyroidism, and 5.6% (n=9) had clinical hypothyroidism, while in the control group, only 1.9% of the patients (n=3) showed signs of subclinical hypothyroidism, and 0.6% (n=1) showed signs of clinical hypothyroidism. In the patients with gallbladder sludge and stone, the prevalence of clinical hypothyroidism was higher than subclinical hypothyroidism.Conclusion: According to the results, hypothyroidism was prevalent in the patients with gallbladder stone and sludge. Therefore, it is recommended that the thyroid function of patients with gallbladder stone and sludge be examined even if the patients do not harbor any other risk factors for the disease.